Different Modulatory Effects of Cognitive Training and Aerobic Exercise on Resting State Functional Connectivity of Entorhinal Cortex in Community-Dwelling Older Adults - Gu, NanNan; Li, Hechun; Cao, Xinyi; Li, Ting; Jiang, Lijuan; Zhang, Han; Zhao, Binglei; Luo, Cheng; Li, Chunbo (Frontiers in Aging Neuroscience, 2021)
The entorhinal cortex (EC) plays an essential role in age-related cognitive decline. However, the effect of functional connectivity (FC) changes between EC and other cerebral cortices on cognitive function remains unclear. The aim of this study was to explore the modulation of two interventions (cognitive training and aerobic exercise) on EC-FC in community-dwelling older adults. In total, 94 healthy older adults aged between 65 and 75 years were assigned to either the cognitive training or aerobic exercise group to receive 24 sessions over 12 weeks, or to a control group. Resting-state functional magnetic resonance imaging was performed at both baseline and 12-month follow-up. Compared to the cognitive training group, the aerobic exercise group showed greater EC-FC in the bilateral middle temporal gyrus, right supramarginal gyrus, left angular gyrus, and right postcentral gyrus. Compared to the control group, the cognitive training group had a decreased EC-FC in the right hippocampus, right middle temporal gyrus, left angular gyrus, and right postcentral gyrus and an increased EC-FC in the bilateral pallidum, while the aerobic exercise group showed increased EC-FC between the right medial prefrontal cortex(mPFC), bilateral pallidum, and right precuneus. Baseline EC-FC in the mPFC was positively correlated with the visuospatial/constructional index score of the Repeatable Battery for the Assessment of Neuropsychological Status. In the cognitive training group, EC-FC value changes in the right hippocampus were negatively correlated with changes in the RBANS delayed memory index score, while in the aerobic exercise group, EC-FC value changes in the left angular gyrus were positively correlated with changes in the RBANS attention index score. These findings support the hypothesis that both cognitive training and aerobic exercise can modulate EC-FC in aging populations but through different neural pathways.